KONTEKSTUALISASI BAHASA QUR’ANI DALAM KOMUNIKASI DAKWAH: STRATEGI TINDAK TUTUR TRANSFORMASI PESAN- PESAN KEAGAMAAN - Lilik Nur Kholidah (Fakultas Sastra Universitas Negeri Malang, 2014)
The success of dakwah as communication activities emphasizing on religious behavior transformation into the society, cannot be separated from the aspects of the language. Islam has taught us about the universal language of dakwah, as mentioned in the Qur'an. Dakwah language based on the Qur'an is characterized by saying something good so that it can imprint on the audience soul. Moreover, it must be a wise, a kind, an easy to understand and sacred words. This paper discusses the organization of dakwah language based on the Qur'an by taking communication strategies that are relevant to its contexts. The use of contextualization in this study means that the activities must consider its situation, including: